Towards A Comprehensive Model For Interpreting Word Order In Classical Biblical Hebrew. (2nd September 2020) - Khan, Geoffrey; Van Der Merwe, Christo H.J.
Abstract: In this paper we examine the function of fronting constructions in verbal clauses in Classical Biblical Hebrew, i.e. constructions that involve the placement of a clause constituent before the verb. We present a model that accommodates the vast majority of cases of fronting in a sample corpus of 1 Samuel. A key feature of our model is the recognition that fronting constructions include both categorical sentences, which make a predication about a base of predication, and also thetic sentences, which present a unitary situation. We classify fronting constructions into three types: (i) narrow constituent focus constructions, (ii) selecting topic constructions, (iii) thetic constructions. An innovative idea that is developed in the paper is that constructions (i) and (iii), although exhibiting different configurations of information structure, nevertheless share various functional properties on the level of discourse organization. On account of these shared properties, we argue that thetic constructions (iii) can be regarded as functional extensions of narrow focus constructions (i). Recognition of these various types of fronting and their interrelationship contributes to a better understanding of the phenomenon.